Tantangan Pendidikan IPS di Era Masyarakat Madani - Edi Susrianto Indra Putra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2022)
In the current era of globalization, technology plays a very important role. The flow of globalization certainly has positive and negative impacts on world society. To anticipate this impact, the role of social sciences education (IPS) is required because social sciences education is very closely related to social issues that occur in society. Apart from that, social studies education learning materials are closely related to the nation's social and cultural values. In solving social problems, social studies education must play an active role. One approach that can be used to solve this social problem is the reflective inquiry approach. Through the reflective inquiry approach, students are taught how to use social skills to solve factual problems that occur in everyday life and in society. Social studies education must be able to help students control themselves in life and apply these values to their behavior in society. Social studies education must be able to develop people into good citizens, familiar with all elements of the environment, wise and prudent in building relationships, and exploring and developing various forms of elements of the existing cultural environment. Social studies education not only emphasizes developing cognitive aspects such as the ability to master social science concepts or theories, the ability to think critically and analytically, or mastering social skills, but can also develop students' affective aspects, which include developing students' attitudes, values, and morals. The reflective inquiry approach will encourage students to use more critical and creative thinking to solve social problems and participate more actively in society. Because the learning material from social sciences education is very closely related to the nation's social and cultural values.